La flore sauvage du boulevard Dr Henri-Henrot à Reims/Durocortorum : approche carpologique de l’environnement du site et des productions de denrées végétales - Véronique Matterne; Clémence Pagnoux (Gallia)
Yielding archaeological levels preserved in water, the excavation of the boulevard Dr. Henri-Henrot represents the best documented site in terms of plant macro-remains for the city of Reims. The site produced a total of 44 retrieved samples, yielding 13,255 remains, including 110 charred and 13,145 soaked (waterlogged) elements, and making it possible to identify 328 different taxa. The incredible wealth represented by the wide spectrum of carpological remains retrieved, is also one of the most extensive for a site from the Roman period in the metropolitan area. It allows us to understand the changes that occurred in the production and consumption of plant foods between the turn of the era and the beginning of the fifth century (around 307 AD), as well as to reconstruct the site’s environment. Five main environment types are represented: cultivated fields and harvesting areas; vacant lots, gardens and weeded crop spaces; meadows and grasslands; waterside vegetation; and hedgerows, forest margins and woodlands. This last category is highly diversified in this case, contrary to what is generally observable for other ancient period sites. This is due to the openness of the environments, as well the anthropic filter, and the preservation of an important part of the carbonized carpological remains. Overall, if we consider the share of native species, which constitute the common background of temperate European plant groups since the beginning of the Holocene, as well as the share of archaeophytes, introduced over the course of history before the discovery of the Americas (Brun 2007), we may discern the marked importance of exogenous species in certain floristic categories. Indeed, of the 233 taxa identified in a sufficiently precise manner, 46% are weeds and 32% are non-native ruderals. Since the Neolithic period, the arrival of these archaeophytes may be considered the result of an extension of their natural zones of dissemination, largely due to the presence and activities of man. This spread by man, originates in the enrichment of domestic species diversity, with the introduction of new food plants, and the opening of real corridors of circulation, through the clearing of plots of land intended for the establishment of areas dedicated to crops. In addition, during the Roman period, the possible circulation of cereal stocks from the Mediterranean via the Rhone corridor to northern France was also a factor (Zech-Matterne 2010). Regardless of the category to which they belong, the ecology of wild species informs us on a variety of human practices. Those associated with cultivated fields (weeds) reflect regular fertilization practices. The index average measuring the sensitivity to nitrogen supply (Julve 1998; Jauzein, Nawrot 2011) is significant of rather rich or amended soils (average of 6 out of 9 for 105 taxa). Nevertheless, the significant variability in condition and setting should be highlighted, as the index includes all values from 1 to 9, a state also recorded for many rural sites of the Roman period in northern France (Zech-Matterne, Brun 2016). The geochemical approach to the question, based on stable nitrogen isotopes, confirmed the diversification of soil reclamation practices during the ancient period, from one site to another but also from one species to another, in Champagne and in the Paris Basin (Aguilera et al. 2017). Two-thirds of the species (n= 85) correspond to annual therophytes that reproduce by seed; winter therophytes (or segetal flora) dominate (31 versus 23 summer ones). These biological types are consistent with the maintenance of cereal crops, preferably sown in autumn. Weeded plants and garden vegetation indicates even richer and more carefully maintained soils, likely improved upon by man, because the average is 7, on a scale of 9 (nitroclinic to nitrophilic plants) for 80 taxa out of 83. The grasslands do not present the same features; the integration of exogenous species remains low; this means that the spontaneously occuring species are not competing with the arrival of archaeophytes, that would find favorable conditions for their perpetuation. Human intervention on the prairies would therefore have remained limited. There is little evidence of controlled burning of grasslands and even less indication of artificial grasslands. The index average measuring the sensitivity to nitrogen supply for 40 of the 49 taxa growing preferentially in grasslands is 5, a value indicative of mesophilic species, i.e. those species which are satisfied with a moderate or intermittent supply of nutrients, but the index oscillates between 1 and 8 on a scale of 9. This enrichment could be the result of natural input from grazing animals. For 45 of the 49 grasslands, the soil moisture sensitivity index is around an average of 6 (hygrophytes) and range from 3 to 9, so they are more likely to have been wet grasslands, possessing variable soil quality and water content. The riverbanks and woodlands were similarly dominated by spontaneous, “natural” wild vegetation. Archaeophytes represent only a minor portion of the species in these categories. Here again, the disturbances caused by human use do not seem to have been of such magnitude as to cause a renewal in vegetation. Several species, not particularly common to the carpological assemblages, were identified, in relationship to the environments mentioned: weakly running waterways not prone to pollution, wet meadows, harvesting areas; the significant wealth of the spectrum, as well as the important number of contexts studied undoubtedly explain the presence of these rare species. Several of them are strictly segetal flora, and accompany limestone soil improvements in harvesting practices. These plants, which are transgressive in their original environments, do not exist naturally in the wild within western Europe; their survival depends on the domestic species they accompany (Jauzein 1995, p. 12). Sometimes attested to since the Neolithic or Bronze Age (Hellmund 2008), species such as Agrostemma githago, or common corn cockle, increased with the emergence of new agricultural practices such as limestone soil improvement. The latter may have favored the migration of plant species from soils with chalky or chalky substrates to soils in the process of alkalization due to repeated tidal flooding (Brasseur et al. 2018). Indeed, a diversity of plants with a facility for growing in more alkaline environments are well represented in the Reims assemblages and become much more so within carpological assemblages in northern France from the Late Iron Age or Roman period onward.